The Influence Of Heart Diet On Cholesterol Levels And Blood Pressure In Patients At Malahayati Islam Hospital Year 2023 - Yusridawati Yusridawati (Jurnal EduHealth, 2023)
the heart muscles caused by narrowing or blockages/plaques in the coronary arteries, or coronary artery atherosclerosis. One of the components that make up this plaque is cholesterol crystals. Data from the Malahayati Islamic Hospital, heart disease is the highest rate, a survey was conducted there were patients who did not eat food from the hospital and they ate food from home. Research Purpose: Knowing the Effect of Heart Diet on Cholesterol Levels and Blood Pressure in Patients at Malahayati Hospital This type of research is a quasi-experimental design with one group pre post test. The population in this study were all heart patients who were treated at the Malahayati Islamic Hospital in Medan. Sampling technique was acidental sampling. The sample size was 10 patients. The data were taken using observation sheets for blood pressure and cholesterol, which were analyzed by paired t-test.The results of the study showed that the majority of blood pressure and cholesterol in heart patients before being given a high heart diet and after being normal. 0.38, SD difference = 1.333 and p value = 0.003. The value of p <0.05 means that H0 is rejected and Ha is accepted, which means that there is a significant difference between the level of cholesterol and blood pressure before and after giving the heart diet to the patient.The conclusion of the study is that there is an effect of giving a heart diet on cholesterol levels and blood pressure in patients at Malahayati Hospital. It is hoped that nurses will inform patients to eat and maintain heart diet foods.